Relevansi Pemikiran Sunan Bonang dalam Pendidikan Modern - Mulyanto, Mulyanto; Solikhah, Hanik Rahmawati; Efendi, Asmira; Mujahidah, Anny Izzatul (Asian Journal of Islamic Studies and Da'wah, 2025)
Sunan Bonang was one of the Walisongo who was very influential in the spread of Islam in Java. As one of the important figures in the history of the spread of Islam, Sunan Bonang is not only known for his preaching, but also for his thoughts and approach to education. As a cleric with deep religious knowledge, Sunan Bonang succeeded in combining Islamic teachings with local culture so that his teachings were easily accepted by the Javanese people, who at that time were still strong in Hindu-Buddhist traditions. Therefore, this research will reveal the relevance of Sunan Bonang education to current education. This research is a library research method with the method of reviewing several literatures in the form of journals and books about Sunan Bonang.